Navigating the city's waterscape: gendering everyday dynamics of water access from multiple sources. Issue 2 (17th February 2021) - Biswas, Durba
ABSTRACT: Large-scale secondary data show that water access is improving in Indian slums; however, women still need to procure water from multiple sources. Based on field research conducted in Coimbatore, Tamil Nadu, this paper examines the everyday negotiations that urban women from slums undertake at different water sources. The study finds that women depend on street taps, water vendors, water tankers, and in-house connections in varying degrees. The results show variation in negotiations that women engage in at multiple sites and sources. These variations have emerged as a result of the characteristics of the water sources and household-level water storage capacity.